2000
DOI: 10.1074/jbc.275.12.8480
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of cAMP-induced Allosteric Changes in Cyclic AMP Receptor Protein from Escherichia coli

Abstract: Cyclic AMP receptor protein (CRP) regulates the expression of several genes in Escherichia coli. The ability of CRP to bind specific DNA sequences and stimulate transcription is achieved as result of binding of an allosteric ligand: cAMP. Stopped-flow fluorimetry was employed to study the kinetics of the conformational changes in CRP induced by cAMP binding to high and low affinity receptor sites. Results of experiments using CRP labeled at Cys-178 with 1,5-I-AENS indicate change in conformation of the helix-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
47
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 26 publications
10
47
1
Order By: Relevance
“…Biochemical and biophysical studies focused on the identification of structural changes accompanying binding of cAMP to CRP have been mostly performed under equilibrium conditions, and much less attention has been paid to the description of the kinetic mechanism of the ligand interaction with CRP. Our previous stopped-flow studies investigating the kinetics of conformational changes in CRP induced by cAMP binding had shown that, at micromolar cAMP concentrations, allosteric changes take place according to a sequential (Koshland-Ném-ethy-Filmer (KNF)) model, whereas conformational changes observed at millimolar concentrations can be described by a concerted (Monod-Wyman-Changeux (MWC)) model (8). The conformational change observed upon binding of cAMP to antisites, described by the KNF model, clearly indicates long-range structural communication between the N-and C-terminal domains of CRP remaining under kinetic control (8).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Biochemical and biophysical studies focused on the identification of structural changes accompanying binding of cAMP to CRP have been mostly performed under equilibrium conditions, and much less attention has been paid to the description of the kinetic mechanism of the ligand interaction with CRP. Our previous stopped-flow studies investigating the kinetics of conformational changes in CRP induced by cAMP binding had shown that, at micromolar cAMP concentrations, allosteric changes take place according to a sequential (Koshland-Ném-ethy-Filmer (KNF)) model, whereas conformational changes observed at millimolar concentrations can be described by a concerted (Monod-Wyman-Changeux (MWC)) model (8). The conformational change observed upon binding of cAMP to antisites, described by the KNF model, clearly indicates long-range structural communication between the N-and C-terminal domains of CRP remaining under kinetic control (8).…”
mentioning
confidence: 99%
“…Our previous stopped-flow studies investigating the kinetics of conformational changes in CRP induced by cAMP binding had shown that, at micromolar cAMP concentrations, allosteric changes take place according to a sequential (Koshland-Ném-ethy-Filmer (KNF)) model, whereas conformational changes observed at millimolar concentrations can be described by a concerted (Monod-Wyman-Changeux (MWC)) model (8). The conformational change observed upon binding of cAMP to antisites, described by the KNF model, clearly indicates long-range structural communication between the N-and C-terminal domains of CRP remaining under kinetic control (8). On the other hand, binding of cAMP to syn-sites of CRP, described by the MWC model, results from displacement of equilibrium between the two structural forms of CRP⅐cAMP 2 , where only one form is able to form a CRP⅐cAMP 4 complex.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that Trp-13 is substantially solventexposed and contributes to ϳ80% of the Trp fluorescence, whereas Trp-85 is buried in the matrix of CRP and contributes to roughly 20% of the Trp fluorescence (44). Results obtained using single-tryptophan-containing CRP mutants indicate that Trp-85 is accountable for the total change observed of the intrinsic Trp fluorescence in wild-type CRP (45). The abovecited reports all strongly suggest that the significant changes on the tryptophan fluorescence in the deletion and the double mutants are most likely attributable to Trp-85.…”
Section: Discussionmentioning
confidence: 56%